(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Esophageal varices (EVs) are a serious consequence of portal hypertension in patients with liver diseases. Several studies have evaluated possible noninvasive markers of EVs to reduce the number of unnecessary endoscopies in patients with cirrhosis but without varices. This prospective study was conducted to evaluate noninvasive predictors of large varices (LV). The study analyzed 100 patients with liver diseases from February 2014 and July 2015. Relevant clinical parameters assessed included Child-Pugh class, ascites etc. Laboratory parameters like hemoglobin level, platelet count, prothrombin time, serum bilirubin, albumin and ultrasonographic characteristics like splenic size, portal vein diameter were assessed. Univariate and multivariate analysis was done on the data for predictors of large EVs. The incidence of large varices were seen in 44. 46%. On multivariate analysis, independent predictors of the presence of LV were palpable spleen, low platelet count, spleen diameter >154 mm, portal vein >13 mm, splenic vein >11.5 mm. Platelet count /spleen diameter <815 had a sensitivity. The presence and higher grades of varices can be predicted by a low platelet count, Child-Pugh class B/C and spleen diameter. These may be considered as non-endoscopic predictors for the diagnosis and management of large grade varices.